ESTABLISHMENT OF EDUCATION DESIGN OF PRINTED MATERIALS IN UKRAINE IN THE FIRST HALF OF THE XX CENTURY - Briukhanova, Halina V. (Educological discourse, 2014)
This article discusses the professional training of specialists in the design of printed materials in the first half of the twentieth century. in Ukraine; problems of continuity, borrowing from a professional design, printing and art education; features training in the design of printed materials in the higher educational institutions of art education. Print design - a huge area of knowledge, the elements of which we can find in any sphere of human activity. Design in any society is closely linked to ethnic culture - customs, traditions, so the cultural component of the program is necessary in education. Modern design, which was created based on the experience of the founders, has some of the contradictions between the requirements for the organization of the educational process and content of vocational training programs in design. In addition, the lack of available training and methodological support, you need to expand the content of design education, and often do not have dedicated in the curriculum hours on mastering the material educational and vocational programs. Article aims to explore the historical periods of training future design specialists of printed materials in Ukraine.